The Media’s Impact on Democratisation and Conflicts in Africa: An Analysis of Recent Trends - Asare-Donkoh, Frankie (International Journal of Mass Communication, 2025)
The fall of the Berlin Wall in 1989, and the end of the Cold War, did not have an effect only on the Germans whose countries were re-united, or the combatants of the Cold War – the United States and the Soviet Union. Rather, the effects of these events affected many countries worldwide, especially developing countries who have since witnessed an unprecedented political and democratic reawakening. As the wave of democratisation continues to move across Africa, conflicts have almost become a by-product, where people, divided on ethnicity and/or religion, fight to establish their presence and dominance in government. One institution associated with the democratisation process and conflicts in Africa is the media. This article reviews some of the democratic processes that have taken place in Africa and the associated conflicts and the role the media have played in both. The article thus contributes to the literature on both democracy in Africa and its associated conflicts and the media’s role. It concludes that, whereas the media played key roles in some conflicts, they have played crucial roles in the promotion of democracy in Africa.